Aromatic plants of Bangladesh : Essential oils of leaves and fruits of Litsea glutinosa (Lour.) C.B. Robinson (Bangladesh Journal of Botany, 2008)
The volatile oil constituents of leaf- and fruit in Litsea glutinosa (Lour.) C.B. Robinson, identified by GC-MS analysis, was 83 and 33, respectively. The major constituents of leaf were phytol (22.42%), caryophyllene (21.48%), thujopsene (12.17%) and Î²-myrcene (5%); while those of the fruit oil contained lauric acid (44.84%), 3-octen-5-yne, 2,7-dimethyl (28.72%), α-cubebene (6.84%) and caryophyllene (5.04%). Key words: Litsea glutinosa, Essential oil, GC-MS, Phytol, Lauric acid doi:10.3329/bjb.v37i1.1568 Bangladesh J. Bot. 37(1): 81-83, 2008 (June)